Pengaruh Citra Destinasi dan Fasilitas Wisata pada Minat Kunjung Wisatawan Taman Margasatwa - Saragi, Charles Parnauli; Prahmana, Shafa Putri; Utami, Nisa Rahmaniyah (Stupa, 2025)
The purpose of this study was to determine the effect of destination image and tourist facilities on the interest of repeat tourists at the Ragunan Wildlife Park tourist attraction. This study used a quantita-tive method with multiple linear regression analysis. The sampling technique used purposive sampling with a sample size of 105 re-spondents. The analysis techniques used were instrument testing, classical assumption testing, and hypothesis testing using IBM SPSS Statistics 25 software. The results of this study indicate that: 1) Des-tination Image partially has a positive and significant effect on the interest in repeat visits to the Ragunan Wildlife Park tourist attrac-tion. 2) Tourist facilities partially have a positive and significant effect on the interest in repeat visits to the Ragunan Wildlife Park tourist attraction. 3) Destination image and tourist facilities simulta-neously have a positive and significant influence on the interest in repeat visits to the Ragunan Wildlife Park tourist attraction.